The Effectiveness of Ergonomic Exercises on Joint Pain Severity among the Elderly - Sugiyarti, Catur; Sulastri, Diah; Dora, Miranti Dea (Inspirasi Foundation, 2025)
Introduction: Joint pain is a prevalent health issue among the elderly, often impairing mobility and quality of life. Non-pharmacological interventions such as ergonomic exercises have gained attention for their safety, accessibility, and potential effectiveness in reducing pain. Objective: This study aimed to evaluate the effect of ergonomic exercise on joint pain intensity among elderly residents at UPTD PSLU Tresna Werdha Natar, South Lampung, in 2025. Methods: A quasi-experimental study with a one-group pre-test and post-test design was conducted. A total of 36 elderly participants aged 60 years and above were recruited using total sampling. Joint pain was assessed using a standardized numerical rating scale ranging from 0 (no pain) to 10 (worst possible pain). Participants engaged in a structured ergonomic exercise program. Pre- and post-intervention pain scores were analyzed using the paired t-test in SPSS. Results: The mean joint pain score prior to the intervention was 2.81 (SD = 0.53), which significantly decreased to 2.08 (SD = 0.50) following the ergonomic exercise program. Statistical analysis showed a significant reduction in pain scores (p < 0.001). Conclusion: Ergonomic exercises demonstrated a significant effect in reducing joint pain among elderly residents. These findings support the integration of ergonomic exercise routines into daily care practices in nursing home settings to enhance elderly well-being and functional independence.